The Influence of Learning Organization and Employee Resilience on Work Engagement at Bumn Bank Branch Office in Bogor - Sholikhah Sholikhah; Reny Nathasya Marbun; Widya Parimita (Program Studi S3 Ilmu Manajemen, 2021)
The purpose of this study are: 1) To determine the description of learning organizations, employee resilience and work engagement to employees of BUMN bank branch offices in Bogor City, 2) To determine the influence of learning organizations on work engagement to employees of BUMN bank branch offices in Bogor City, 3) To determine the effect of employee resilience on work engagement to employees of BUMN bank branch offices in Bogor City, 4) To determine the prediction of the learning organization and employee resilience research model to work engagement to employees of BUMN bank branch office in Bogor City. This research was conducted on 200 employees of BUMN bank branch office in Bogor City. The technique used in data collection is the survey method by distributing questionnaires then processed using the SPSS 24 program. This study uses descriptive analysis and ex post facto. The results of the regression show that there is a positive and significant influence between learning organizations on work engagement, employee resilience to work engagement and research models of learning organizations and employee resilience can predict work engagement to employees of BUMN bank branch offices in Bogor City with Fcount> Ftable (19,157> 3.04) and significance (0.000 <0.05).